Distribution of I-125-labeled crotamine in mice tissues - Boni-Mitake, M.; Costa, H.; Vassilleff, S.; Rogero, J. R. (Elsevier B.V., 2006)
Crotamine is a strong basic polypeptide from Crotalus durissus terrificus (Cdt) venom composed of 42 amino acid residues tightly bound by three disulfide bonds. It causes skeletal muscle spasms leading to spastic paralysis of hind limbs in mice. The objective of this paper was to study the distribution of crotamine injected intraperitoneally (ip) in mice. Crotamine was purified from Cdt venom by gel filtration, followed by ion exchange chromatography, using a fast-performance liquid chromatography (FPLC) system. Purified crotamine was irradiated at 2 kGy in order to detoxify. Both native and irradiated proteins were labeled with 125, using chloramine T method, and separated by get filtration. Male Swiss mice were injected ip with 0.1 mL (2 x 10(6) cpm/mouse) of I-125 native or irradiated crotamine. At various time intervals, the animals were killed by ether inhalation and blood, spleen, liver, kidneys, brain, lungs, heart, and skeletal muscle were collected in order to determine the radioactivity content. The highest levels of radioactivity were found in the kidneys and the liver, and the lowest in the brain. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: crotamine; toxin; biodistribution; Crotalus; venom; gamma radiation